2017
DOI: 10.1186/s12917-017-1053-0
|View full text |Cite
|
Sign up to set email alerts
|

Omental adipose tissue is a more suitable source of canine Mesenchymal stem cells

Abstract: BackgroundMesenchymal Stem Cells (MSCs) are a promising therapeutic tool in veterinary medicine. Currently the subcutaneous adipose tissue is the leading source of MSCs in dogs. MSCs derived from distinct fat depots have shown dissimilarities in their accessibility and therapeutic potential. The aims of our work were to determine the suitability of omental adipose tissue as a source of MSCs, according to sampling success, cell yield and paracrine properties of isolated cells, and compared to subcutaneous adipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 55 publications
5
34
0
Order By: Relevance
“…It is well-known that MSC populations are intrinsically heterogeneous what can significantly impact their therapeutic potency ( 37 ). Besides different factors, such as MSC source ( 19 , 21 , 23 , 38 ), tissue collection site ( 39 41 ), animal age ( 39 , 42 44 ), and the number of passages ( 45 48 ) that have been demonstrated to affect MSC characteristics ex vivo , animal species could likely also influence MSC potency. Only a few studies compared MSCs between species directly ( 49 51 ), while it is difficult to draw any comparisons between different studies using cells from different species because of the lack of standardization of methods for the isolation, culture, and characterization of animal MSCs.…”
Section: Introductionmentioning
confidence: 99%
“…It is well-known that MSC populations are intrinsically heterogeneous what can significantly impact their therapeutic potency ( 37 ). Besides different factors, such as MSC source ( 19 , 21 , 23 , 38 ), tissue collection site ( 39 41 ), animal age ( 39 , 42 44 ), and the number of passages ( 45 48 ) that have been demonstrated to affect MSC characteristics ex vivo , animal species could likely also influence MSC potency. Only a few studies compared MSCs between species directly ( 49 51 ), while it is difficult to draw any comparisons between different studies using cells from different species because of the lack of standardization of methods for the isolation, culture, and characterization of animal MSCs.…”
Section: Introductionmentioning
confidence: 99%
“…These beneficial effects can also be related to other mechanisms of stem cell action such as inhibition of effector T-cell proliferation and the expression of inflammatory cytokines by expansion of regulatory T-cells and the production of interleukin-10 [42,43]. Moreover, the action of soluble ASCs factors [44][45][46] and/or the secretion of paracrine growth factors that can correct several pathophysiological alterations cannot be ruled out [47].…”
Section: Discussionmentioning
confidence: 99%
“…The source of adipose tissue used for SVF in our study varied among patients. Multiple studies in dogs and people have shown differences in MSC yield as well as replication rate and differentiation ability of MSC depending on the source of adipose tissue (eg, omental versus SC) . Thus, functional variation may exist among MSC derived from different adipose sites and may affect their regenerative and reparative capacities.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies in dogs and people have shown differences in MSC yield as well as replication rate and differentiation ability of MSC depending on the source of adipose tissue (eg, omental versus SC). [36][37][38][39] Thus, functional variation may exist among MSC derived from different adipose sites and may affect their regenerative and reparative capacities. Future studies of this nature are needed in cats in which the source of adipose-derived MSC is kept consistent to determine whether adipose origin is an important variable.…”
Section: Discussionmentioning
confidence: 99%